A Study of Jordan bi-derivations in Prime rings with parameters (α, β) - Dr.S.Lalitha (Utilitas Mathematica, 2024)
Assume thatS is a prime ring with α and β as automorphisms. Bi-additive mapping If then D is a (α, β) Jordan bi-derivation. In this study, the researcher determines the circumstances in which a symmetric Jordan bi-derivation (α, β) transforms into a symmetric bi-derivation (α, β). Furthermore, we characterise the symmetric Jordan bi-derivations (α, β).